THE INFLUENCE OF THE APPLICATION OF QUANTUM LEARNING ASSISTED BY ISLAMIC CHARACTER MEDIA ON THE RESPONSIBILITY AND LEARNING OUTCOMES OF STUDENTS IN GRADE V SDN PRAMPELAN - Muhamad Afandi; Yulina Ismiyanti; Sri Wahyuningsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The study aims at determining the effect of the implementation of the quantum learning model assisted by Islamic-character learning media on the responsibilities and learning outcomes of the fifth graders at Prampelan Elementary School. This research used is pre-experimental design. The results showed that there was an effect of learning responsibilities on the implementation of the quantum learning model assisted by Islamic character learning media influencing student learning outcomes, 51.8%. Meanwhile, the remaining of learning outcomes, 48.2% of student learning outcomes could be explained by other variables outside this study. Based on the classical completeness test that students in Grade VA at SDN Prampelan with a quantum learning model assisted by Islamic learning media with a value of ≥ 65 has reached 75%.